Memoria oral en mayores : entre trochas y caminos, hacia la recuperación de la tierra y el fortalecimiento de la organización indígena en el departamento de Caldas (2007)
ABSTRACT: This text presents the projection of a group of students in their community in the Indigenous tribe of Cañamomo Lamaprieta, in the municipalities of Riosucio and Supía, Caldas, looking at understanding and learning from the processes of community organization and defense of the territory, lead by their elders in the last decades of the 20th century. The project looks at stopping the state of marginalization that, given the weakening of oral traditions and the death of the elders, covers experiences on the educational, organizational areas and resilience struggles for the recovery of land in such communities.